Effectiveness of 10-valent pneumococcal conjugate vaccine against vaccine-type invasive pneumococcal disease in Pakistan. (March 2019) - Riaz, Atif; Mohiuddin, Syed; Husain, Sara; Yousafzai, Mohammad Tahir; Sajid, Muhammad; Kabir, Furqan; Rehman, Najeeb ur; Mirza, Waseem; Salam, Basit; Nadeem, Naila; Pardhan, Khatidja; Khan, Khalid Mehmood A.; et al.
Highlights: This is the first study to provide estimates of 10-valent pneumococcal conjugate vaccine (PCV10) effectiveness in a South Asian country. The study showed strong effectiveness with three doses of vaccine given at 6, 10, and 14 weeks of age. The results are encouraging for the sustained use of PCV10 in Pakistan and other South Asian countries considering introduction of the vaccine. Abstract: Objective: To assess the effectiveness of 10-valent pneumococcal conjugate vaccine (PCV10) against invasive pneumococcal disease (IPD) due to vaccine serotypes of Streptococcus pneumoniae post introduction of the vaccine into the routine immunization program in Pakistan. Methods: A matched case–control study was conducted at 16 hospitals in Sindh Province, Pakistan. Children aged <5 years (eligible to receive PCV10) who presented with radiographically confirmed pneumonia and/or meningitis were enrolled as cases. PCR for the lytA gene was conducted on blood (for radiographic pneumonia) and cerebrospinal fluid (for meningitis) samples to detect S. pneumoniae . The proportion of IPD due to vaccine serotypes (including vaccine-related serogroups) was determined through serial multiplex PCR. For each case, at least five controls were enrolled from children hospitalized at the same institution, matched for age, district, and season. Results: Of 92 IPD patients enrolled during July 2013 to March 2017, 24 (26.0%) had disease caused by vaccine serotypes. Most case (87.5% of 24) and control (66.4% of 134) children had not received any PCV10 doses. The estimated effectiveness of PCV10 against vaccine-type IPD was 72.7% (95% confidence interval (CI) −7.2% to 92.6%) with at least one dose, 78.8% (95% CI −11.9% to 96.0%) for at least two doses, and 81.9% (95% CI −55.7% to 97.9%) for all three doses of vaccine. Conclusions: The vaccine effectiveness point estimates for PCV10 were high and increased with increasing number of doses. However, vaccine effectiveness estimates did not reach statistical significance, possibly due to low power. The findings indicate the likely impact of vaccine in reducing the burden of vaccine-type IPD if vaccine uptake can be improved.